2000
DOI: 10.1046/j.1471-4159.2000.0750373.x
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific Phosphorylation of Neurofilament‐L Is Mediated by Calcium/Calmodulin‐Dependent Protein Kinase II in the Apical Dendrites During Long‐Term Potentiation

Abstract: Neurofilament-L (NF-L), one subunit of the neuronal intermediate filaments, is a major element of neuronal cytoskeletons. The dynamics of NF-L are regulated by phosphorylation of its head domain. The phosphorylation sites of the NF-L head domain by protein kinase A, protein kinase C, and Rho-associated kinase have been previously identified, and those by calcium/ calmodulin-dependent protein kinase II (CaMKII) were identified in this study. A series of site-and phosphorylation state-specific antibodies against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 54 publications
0
50
0
Order By: Relevance
“…The head domains of NFL, NFM, NFH and a-internexin are phosphorylated and glycosylated (Dong et al, 1996;Manser et al, 2008;Tanaka et al, 1993;Vosseller et al, 2006). Phosphorylation of the NF head domain is mediated by the second messenger dependent kinases protein kinase A (PKA) and C (PKC) (Sihag et al, 1988;Sihag and Nixon, 1989;Sihag and Nixon, 1990) and possibly also by Cam kinase II (Hashimoto et al, 2000). The occurrence of NF head phosphorylation in the cell body soon after subunit synthesis reflects its suggested role in maintaining the disassembled state of NFs, as head phosphorylation of NFL inhibits NF assembly (Hashimoto et al, 2000;Hisanaga et al, 1990;Sihag et al, 1999;Sihag and Nixon, 1991).…”
Section: Neurofilament Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The head domains of NFL, NFM, NFH and a-internexin are phosphorylated and glycosylated (Dong et al, 1996;Manser et al, 2008;Tanaka et al, 1993;Vosseller et al, 2006). Phosphorylation of the NF head domain is mediated by the second messenger dependent kinases protein kinase A (PKA) and C (PKC) (Sihag et al, 1988;Sihag and Nixon, 1989;Sihag and Nixon, 1990) and possibly also by Cam kinase II (Hashimoto et al, 2000). The occurrence of NF head phosphorylation in the cell body soon after subunit synthesis reflects its suggested role in maintaining the disassembled state of NFs, as head phosphorylation of NFL inhibits NF assembly (Hashimoto et al, 2000;Hisanaga et al, 1990;Sihag et al, 1999;Sihag and Nixon, 1991).…”
Section: Neurofilament Phosphorylationmentioning
confidence: 99%
“…Phosphorylation of the NF head domain is mediated by the second messenger dependent kinases protein kinase A (PKA) and C (PKC) (Sihag et al, 1988;Sihag and Nixon, 1989;Sihag and Nixon, 1990) and possibly also by Cam kinase II (Hashimoto et al, 2000). The occurrence of NF head phosphorylation in the cell body soon after subunit synthesis reflects its suggested role in maintaining the disassembled state of NFs, as head phosphorylation of NFL inhibits NF assembly (Hashimoto et al, 2000;Hisanaga et al, 1990;Sihag et al, 1999;Sihag and Nixon, 1991). Phosphorylation of the NF head domain is also known to modulate their interaction with fodrin, an important protein of the sub-axolemmal cytoskeleton (Frappier et al, 1987).…”
Section: Neurofilament Phosphorylationmentioning
confidence: 99%
“…NF proteins, in particular NF-M and NF-H, are phosphorylated extensively, with highly conserved phosphorylation sites (Julien and Mushynski, 1983;Carden et al, 1985;Schlaepfer, 1987). It is suggested that the phosphorylation plays an important role in stabilizing and continuously remodeling NF filaments during the axonal growth and might be connected to plasticity of both axons and dendrites (Schlaepfer, 1987;Wang et al, 1994;Hashimoto et al, 2000;Posmantur et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Ser-501 is in the SP sequence followed by Lys at the third C-terminal site. The SPXK sequence is a consensus phosphorylation motif for Cdk5 (17,18,20) and also mitogenactivated protein kinase. Because Ala substitution of Ser-501 reduced the phosphorylation of the E-segment by Cdk5 and ERK (data not shown), we suggest that this site would be phosphorylated by Cdk5 and ERK.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of the head domain by second messenger-dependent protein kinases induces filament disassembly in vitro (13)(14)(15). Nascent NF-L is phosphorylated at Ser-55 by PKA until incorporation into the axonal NF network (16) and at Ser-57 by calcium/calmodulin-dependent protein kinase II (CaMKII) at apical dendrites of the pyramidal neurons in a hippocampal slice culture when long term potentiation is induced (17). The long C-terminal tail domains of two larger subunits, NF-M and NF-H, are highly phosphorylated in axons.…”
mentioning
confidence: 99%